Environmental quality analysis for sustainable urban public green spaces management in Bartın, Turkey - Cengiz, Canan; Cengiz, Bülent; Bekci, Banu; Cengiz, Bülent; Cengiz, Canan (WFL Publisher Ltd., 2012)
Urban green areas with their diverse forms such as public spaces, urban parks and private gardens, might significantly affect the quality of urban environment and urban life. Environmental quality is one of the main aspects of livable and sustainable cities. This paper focuses on the significance of urban public green spaces in environmental quality. Conducted in the city of Barti{dotless}n located in the Western Black Sea Region of Turkey, this study analyzes five different urban public green spaces in terms of sustainable urban fabric and environmental quality. The study consists of three main stages: i) survey study (evaluation of urban public green spaces recreational use preferences and the selected areas according to user preferences) ii) examination of the behavior maps of the research areas, and iii) evaluation of the environmental quality analysis of these areas. For this purpose, a survey was conducted with 150 and behavior maps were produced separately for each research area. Expert opinion was also included within the analysis of environmental quality. The study concludes with a discussion on the environmental quality of urban public green spaces and some recommendations for urban green space management. © 2020 Elsevier B.V., All rights reserved.
Keywords: Bartin; Environmental Quality; Landscape Management; Urban Public Green Spaces; User Preference